2000
DOI: 10.1042/0264-6021:3500061
|View full text |Cite
|
Sign up to set email alerts
|

Malonyl-CoA metabolism in cardiac myocytes

Abstract: (1) Malonyl-CoA is thought to play a signalling role in fuel-selection in cardiac muscle, but the rate at which the concentration of this potential signal can be changed has not previously been investigated. (2) Rapid changes in cellular malonyl-CoA could be observed when rat cardiac myocytes were incubated in glucose-free medium followed by re-addition of 5 mM glucose, or when cells were transferred from a medium containing glucose to a glucose-free medium. On addition of glucose, malonyl-CoA increased by 62%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
(60 reference statements)
1
21
0
1
Order By: Relevance
“…By contrast, the presence of cytosolic MCD activity in heart was reported (71). Both of these studies (55,71), as well as a third study (30), reported the existence of overt mitochondrial MCD activity, which is between 16% and 23% of the total heart mitochondrial MCD activity and which ought to the accessible to cytosolic malonylCoA. The question of how and where this overt MCD is attached to heart mitochondrial membrane lipids or to membrane proteins remains unresolved.…”
Section: The Subcellular Distribution and Regulation Of Malonyl-coa Dmentioning
confidence: 77%
See 1 more Smart Citation
“…By contrast, the presence of cytosolic MCD activity in heart was reported (71). Both of these studies (55,71), as well as a third study (30), reported the existence of overt mitochondrial MCD activity, which is between 16% and 23% of the total heart mitochondrial MCD activity and which ought to the accessible to cytosolic malonylCoA. The question of how and where this overt MCD is attached to heart mitochondrial membrane lipids or to membrane proteins remains unresolved.…”
Section: The Subcellular Distribution and Regulation Of Malonyl-coa Dmentioning
confidence: 77%
“…In rat heart, MCD activity was observed in a crude mitochondrial fraction but no evidence was found for a cytosolic MCD (55). By contrast, the presence of cytosolic MCD activity in heart was reported (71).…”
Section: The Subcellular Distribution and Regulation Of Malonyl-coa Dmentioning
confidence: 81%
“…It is important to note that the inhibitory site for malonyl-CoA is on the cytosolic side of CPT I (12,15,22,40) and that malonyl-CoA is found in both the cytosol and the mitochondria (12,15,22,40). It is possible that adrenergic stimulation and/or high rates of cardiac energy expenditure cause a selective decrease in cytosolic acetyl-CoA or result in selective alterations in the activity or cellular location of cytosolic ACC or MCD, which lead to reduced production or greater clearance of cytosolic malonyl-CoA.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, increases in carbohydrate fuels together with an increase in insulin results in decreased fatty acid oxidation and an increase in malonyl-CoA appears to be the key factor in this reverse Randle Cycle effect. The content of malonylCoA in perfused heart or in cardiac myocytes is increased by glucose [11] and it has been suggested that the increase in malonylCoA is due to an increased supply of acetyl-CoA for ACC [34]. We propose that dephosphorylation and activation of ACC in response to glucose (Figure 3) additionally contributes to this reverse Randle Cycle effect.…”
Section: Discussionmentioning
confidence: 71%